Factors influencing customer satisfaction and loyalty to internationally branded clothes - Wong, Foong Yee; Low, Koa Er (Universiti Putra Malaysia Press, 2013)
Satisfaction is important as the principle purpose of a business is to create satisfied customers that will consequently lead to higher profitability in the future. Therefore, it is crucial for marketers to focus on creating and retaining customer loyalty in a business. Besides, customer satisfaction and loyalty are being highlighted due to growing interests and practices in customer relationship management. Thus, this study seeks to examine the factors affecting customer satisfaction with regard to the purchase of imported apparel, and to determine the relationship between customer satisfaction and customer loyalty. A questionnaire was constructed and data were collected from 100 buyers of imported apparel in Malaysia. Results indicated that customer satisfaction is positively affected by brand credibility, perceived quality, and perceived value. This finding implies that a higher customer satisfaction leads to higher levels of customer retention and loyalty towards a specific brand. In conclusion, understanding such factors will help marketers of internationally branded apparel to operate their businesses effectively.